Fracture resistance of bovine incisors restored with different glass fiber posts: Effect of the diameter of fiber post - Lucas Villaça Zogheib; Luis Gustavo Oliveira Vasconcellos; Ana Carolina Rodrigues Danzi Salvia; Ivan Balducci; Clovis Pagani; Marco Antonio Bottino; Luiz Felipe Valandro (Wolters Kluwer Medknow Publications, 2012)
Aim: Compare the effect of three post designs on the fracture resistance and failure modes of composite core - fiber post - crownless tooth sets. Materials and Methods: Ninety bovine incisors were selected and divided into nine groups of 10 specimens. The teeth were assigned to three groups based on the post design: Cylindrical, tapered, and double-tapered. Each group was subdivided into three subgroups in accordance with the diameter of the post: Small (No.1), medium (No.2), and large (No.3). The Panavia F system was used for post cementation. The specimens were mounted in acrylic resin blocks with a layer of silicone rubber covering the roots. A universal testing machine compressively loaded the specimens from the palatal side at a crosshead speed of 1 mm/min and at an angle of 135Ί to the long axis of the teeth, until failure occurred. The failure mode was determined by a stereomicroscope inspection of all the specimens. Data were analyzed by one-way ANOVA and the Tukey test (P < 0.05). Results: The fracture resistance was affected by the type of post (P < 0.0001). A narrower diameter for all of the post systems allowed for higher resistance. The main failure mode in the large cylindrical group was catastrophic fractures, while the main failures in the other eight groups were favorable. Conclusion: Narrower diameter posts showed higher fracture resistance. The dominant failure pattern was repairable fracture, except for those with large cylindrical groups.